Predictive values of morphological and motor system for sprint selection purposes - Mihajlovic, I.; Toncev, I. (Acta Kinesiologica, 2008)
There are some difficulties in the process of selection in athletics, especially in sprint since the dominant skill is speed, which is in a large correlation with genetics. Timely and proper selection is in a causal connection with the age which makes adequacy of that kind of methodological procedure even more difficult. Wishing to give a small contribution at choice for adequate tests for the purpose of selection, a research was realized during which some appropriate and responsible tests for sprint running were applied. In that way, some predictive values for a successful selection were acquired.